"THERAPY WITH FLOWERS OF VARIOUS COLORS: A STUDY: ‘‘विविध रंगों के फूलों से चिकित्सा: एक अध्ययन - Joshi, Shobhana; Khandwe, Kirti (International Journal of Research -GRANTHAALAYAH, 2014)
The priceless gift given by God to human lovers is included in the beautiful flowers of nature. The flower itself is a poem in itself. Flowers are rich in many mineral salts. Flowers vary from season to season. Flowers are the softest product of nature. The flower is the carrier of emotions. The flower is a symbol of love with its beauty, aroma, tenderness. Is also the communicator of love. The flower is vibrant. The basis of expression of depth of emotions is the flower itself. Flower is the bridge between the devotee and God. Vandana is the medium. Flowers are the main ingredient of devotion in Bhagavat worship. Flower means flower with its five qualities, beauty, color, softness, smell and pollen. It is a source of joy. It is the father of attraction. Beautiful expression of nature. Symbol of feelings, flower in the gift of nature is also a means of treatment of many diseases. Effectiveness of diseases in flower medicine is important from every point of view. Color is an integral part of human culture. Along with the color, its aroma has a profound effect on the mind. With their glimpses, the body and mind become cheerful. ईश्वर के द्वारा मानव प्रेमियों को दिया गया अमूल्य उपहार ‘फूल’ की प्रकृति की खूबसूरत नेमतों में शामिल है। फूल स्वयं अपने आप में एक कविता सा है। फूलों अनेक खनिज-लवणों से भरपूर होते है। हर मौसम के फूल अलग-अलग होते है।प्रकृति का कोमलतम उपादान है फूल। फूल भावनाओं का वाहक है। फूल प्रतीक है अपनी सुंदरता, सुगंध, कोमलता के साथ प्रेम का प्रतीक है। प्रेम का संदेश वाहक भी है। फूल जीवंत है। भावनाओं की गहराई के अभिव्यक्ति का आधार फूल ही है। भक्त एवं भगवान के बीच का सेतु है फूल। वंदना का माध्यम है। भगवत् आराधना में समर्पण का मुख्य उपादान है फूल। पुष्प अर्थात् फूल अपने पाँच गुणों, सौंदर्य, रंग, कोमलता, गंध और पराग के साथ क्रिया रुप है। आनंद का पोषक है। यह आकर्षण का जनक है। प्रकृति की सुंदर अभिव्यंजना है।भावनाओं के प्रतीक, प्रकृति के उपहार में फूल अनेक रोगों के उपचार के साधन भी है फूल चिकित्सा में रोगों की प्रभावशीलता हर दृष्टिकोण से महत्वपूर्ण है। रंग मानव संस्कृति का अभिन्न हिस्सा है। रंग के साथ-साथ उसकी सुंगध मन-मस्तिष्क पर गहरा प्रभाव डालती है। इनकी झलक भर से तन-मन प्रफुल्लित हो जाता है।